Educational Game Wordwall for Enhancing Daily Face Makeup Competencies of Class X Students at Vocational High School in Beauty Cosmetology Program - Putriana, Megawati Eko; Sutopo, Yeri; Usman, Nur Qudus (Universitas Negeri Semarang, 2024)
This study aims to develop educational media in the form of a web-based game using Wordwall, focused on teaching daily face makeup skills at Vocational High School 4 Yogyakarta. The primary issues addressed in this research include the use of a less interactive lecture-based method, low student learning outcomes falling below the Minimum Completion Criteria, and the underutilization of technology in the learning process. The research follows the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The media was designed to encourage unconscious learning and improve students learning outcomes. Validation was conducted by subject matter and media experts, while its practicality was tested by both teachers and students. The validation results revealed that the media is highly feasible, with an average score of 4.84, while the practicality test achieved a score of 97.3%, categorized as very practical. The effectiveness test, using N-Gain analysis and independent sample t-tests, demonstrated a significant improvement in student learning outcomes. Therefore, the Wordwall educational game media is considered valid, practical, and effective for use in the Beauty Cosmetology program. This media can serve as an innovative solution to enhance the quality of both the teaching process and student learning outcomes at vocational high schools.